Revitalizing the Muslim Community through the Integration of Islamic Education and Science: An Analysis from the Perspective of State Islamic University Academics - Suhernawati Suhernawati; Alma’arif Alma’arif; Elya Susanti; Fatimah Uri (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines four models of integration between Islam and science in Islamic higher education institutions in Indonesia using a qualitative approach and literature review, namely the Amin Abdullah Integration-Interconnection model, Imam Suprayogo’s Tree of Knowledge model, the Revelation Guides Knowledge (WMI) model, and the Andromeda Spiral model. The results show that although these models have different epistemological orientations, they complement each other by emphasizing interdisciplinary dialogue, tauhid as the foundation of the curriculum, the supremacy of revelation, and the progressive dynamics of knowledge. Despite challenges such as limited resources and implementation difficulties, there are strategic opportunities through interdisciplinary research, curriculum innovation, maqashid shariah approaches, and the dissemination of integrative paradigms. In conclusion, knowledge-based Islamic education plays a crucial role in shaping Muslim generations who are religious, intellectual, and contributive, with these four models serving as an epistemological map that unites revelation, philosophy, curriculum, and a vision of civilization.